Object Processing in the Infant: Lessons from Neuroscience - Wilcox, Teresa (Trends Cogn Sci, 2015)
Object identification is a fundamental cognitive capacity that forms the basis for more complex thought and behavior. The adult cortex is organized into functionally distinct visual object-processing pathways that mediate this ability. Insights into the origin of these pathways have begun to emerge through the use of neuroimaging techniques with infant populations. The outcome of this work supports the view that, from the early days of life, object-processing pathways are organized in a way that resembles that of the adult. At the same time, theoretically important changes in patterns of cortical activation are observed during the first year. These findings lead to a new understanding of the cognitive and neural architecture that supports infants’ emerging object-processing capacities.